Indefessae labor limae Sepulvedanae en los libros 19 y 20 de la De rebus gestis Caroli quinti historia - José Antonio Bellido Díaz (Exemplaria Classica, 2008)
In the two manuscripts of Sepúlveda’s De rebus gestis Caroli quinti historia, dating from his own time, we can see the annotations and the corrections that the author made while he was revising his greatest work. In this article the different stages of the intervention of the author in both manuscripts and the reasons for which he did so, basically in order to preserve the latinitas and to achieve a clearer expression, as well as a more refined style, are studied.